Optimization of mortars containing steel scale using Taguchi based grey relational analysis method - Arici, Erdinc; Kelestemur, Oguzhan (Elsevier Sci Ltd, 2019)
This paper examined the performance of cement mortars containing steel scale as experimentally and statistically. To this end, mortar samples with different levels of fine scale (0%, 5%, 10%, 15%), coarse scale (0%, 5%, 10%, 15%), water/cement ratio (0.5, 0.6) and cement dosage (400 kg/m(3), 500 kg/m(3)) were produced and their compressive strength, flexural tensile strength and porosity value were determined. Taguchi based grey relational analysis method was performed to obtain optimal parameter levels for simultaneously achieving the desired properties of the mortars. L-16 (4(2) x 2(2)) orthogonal array table was chosen for the tests according to the Taguchi quality design concept. ANOVA (Analysis of variance) method was applied to determine statistically effects of the parameters. Optimization results were compared with initial parameters (control sample) and it was concluded that there was a good fit between them. Based on the overall observations, it is recommended that the Taguchi based grey relational analysis method could be effectively used in such studies. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Cement mortar; Steel scale; Taguchi design; Grey relational analysis; Optimization